Chronic Kidney Disease (CKD) classification for low-resource settings: Taking into account patients’ social vulnerability (2024)
Introduction: Chronic kidney disease (CKD) has increasingly become a significant public health problem and economic burden for health systemsworldwide. In addition, social vulnerability (SV) can also contribute to the high burden of chronic kidney disease. Contents: Social vulnerability can be explored by evaluating five dimensions: household composition, income, unstable housing, segregation, and immigration status, proposed by Jimenez- Garcia et al. Conclusions: Based on these variables a social vulnerability index score (SOVI) was described. This article proposes integrating the social vulnerability index score into the CKD-KDIGO classification in order to provide a more comprehensive approach to the problem of chronic kidney disease burden, with the goal of promoting kidney health an improving current kidney prevention programs.